The influence of social class of origin on labor market entry and the mediating role of education in Italy - Davide Bussi; Carlotta Piazzoni; Marta G. Pancheva; Mario Lucchini (Frontiers in Sociology)
IntroductionAccess to the labor market is influenced by various socio-economic factors, including social class and education. In Italy, these elements play a crucial role in determining employment opportunities and career trajectories. This study aims to analyze how social origin influences transition to the first job across different birth cohorts, gender groups, and macro-region of residence while also assessing the mediating role of education.MethodsUsing Event History Analysis, we estimate labor market entry timing via survival models and discrete-time logistic regression, accounting for social background effects. We classify social origin using the European Socio-economic Classification scale based on the parental occupation. The analysis, conducted separately by gender, controls for birth cohort, education, parenthood, and area of residence. Also, we employ the KHB decomposition, which enables us to quantify the extent to which education mediates the influence of social background on labor market entry.ResultsIndividuals from lower social backgrounds enter the labor market earlier, while those from higher-status families tend to delay entry, likely due to extended education and greater financial support. Educational attainment mediates the relationship between social origin and labor market entry, as individuals from higher-status backgrounds tend to delay entry due to prolonged education. However, education does not fully eliminate class-based disparities—controlling for educational attainment amplifies rather than erases the effect of social origin, indicating that other mechanisms still play a role. Social class disparities in labor market entry remain largely stable across cohorts, with only minimal convergence among men and no significant change among women. For men, class effects remain stable across macro-regions, while for women they are stronger in northern Italy.DiscussionOur findings confirm that social origin remains a significant determinant of labor market entry in Italy, despite changes in education and labor market structures over time. While increased access to education has contributed to greater opportunities, it has not entirely eliminated class-based disparities in employment transitions.